Kensington (Jamaica : [Publisher not identified ], 1858)
A diagram representing 358 acres formerly part of Belle Vue Plantation conveyeed to Wm. Finlason by Edward F. Muschett. Surveyed by Henry Forbes, Dec. 6th, 1858.
Keywords: Maps; Jamaica -- Maps; St. Elizabeth